Pertimbangan Hakim dalam Memberikan Putusan pada Kasus Pembunuhan Begal untuk Melindungi Diri - Hasan, Sawia (Penerbit Goodwood, 2024)
Purpose: This research aims to analyze the judge's legal reasoning in a murder case involving self-defense by a minor, specifically evaluating the application of Article 49 of the Indonesian Criminal Code (KUHP) on necessary defense (noodweer), and assessing whether the verdict adhered to the principles of justice, benefit, and legal certainty. Research methodology: The study employs normative legal research with conceptual and case approaches. Legal materials include primary sources (statutory provisions and court rulings), secondary sources (books and journal articles), and tertiary sources (legal encyclopedias and dictionaries). Data collection was conducted through literature and document analysis, and the data were examined using statutory interpretation, legal theory, and jurisprudential review. Results: The findings indicate that the judge's decision to convict the minor under Article 351(3) KUHP for causing death through violence did not adequately consider the relevance of Article 49 KUHP regarding self-defense. The court focused on the delay between the threat and the act of defense, neglecting the child's psychological condition and the urgency of the situation. Although based on prosecutorial evidence, the verdict failed to incorporate contextual factors such as fear, coercion, and instinctive reaction, which were critical in triggering the defendant’s response. Conclusions: The judicial reasoning lacked depth in examining the mental and emotional state of the minor, reflecting a rigid interpretation of the law that may compromise restorative justice and child-sensitive adjudication. Limitations: The study is limited to a single judicial decision and does not incorporate empirical data or psychological expert assessments, limiting the analysis of mental condition and its legal implications. Contribution: This research highlights the importance of contextual and psychological analysis in judicial discretion for cases involving minors and contributes to the discourse on fair application of self-defense provisions in Indonesian criminal law.